Rethinking EU Cohesion Policy - Asatryan, Zareh; Birkholz, Carlo; Heinemann, Friedrich (ZEW policy brief, 2024)
Cohesion Policy (CP) has been a central economic policy tool of the EU for several decades. In the current context of fundamental challenges facing the EU, and ahead of the next seven-year budgetary cycle, Europe has the opportunity to rethink and reform the EU budget and CP in particular. This policy brief condenses the insights from a large research project on CP aiming to contribute to this reform debate. The report was prepared by a group of European experts with the support of the German Federal Ministry of Finance and consists of 14 stand-alone chapters. These chapters contribute to the following three broad questions: What are the fundamental rationales for CP today and what should the future path of this policy look like in a changing environment? What do we know about the impact of over 30 years of CP in the light of its objectives? And what are the key constraints and enablers for a successful CP?
Keywords: Graue Literatur